2018
DOI: 10.1002/stem.2775
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Human Photoreceptor Precursors via a Cell Surface Marker Panel from Stem Cell-Derived Retinal Organoids and Fetal Retinae

Abstract: Loss of photoreceptor cells due to retinal degeneration is one of the main causes of blindness in the developed world. Although there is currently no effective treatment, cell replacement therapy using stem‐cell‐derived photoreceptor cells may be a feasible future treatment option. In order to ensure safety and efficacy of this approach, robust cell isolation and purification protocols must be developed. To this end, we previously developed a biomarker panel for the isolation of mouse photoreceptor precursors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 33 publications
4
68
1
Order By: Relevance
“…The establishment of reference transcriptome maps for individual cell types in the retina provide unprecedented insights into the signals that define retinal cell identity and advance our understanding of the retina. This human neural retina transcriptome data can be used as a benchmark to assess the quality and maturity of pluripotent stem cell-derived retinal cells, such as retinal ganglion cells (Gill et al, 2016;Kobayashi et al, 2018;Sluch et al, 2015) and photoreceptors (Lakowski et al, 2018). We also confirmed that a relatively low level of sequencing depth (~40,232 reads per cell) is sufficient for identification and classification of major cell types in a complex tissue like retina.…”
Section: Discussionsupporting
confidence: 63%
“…The establishment of reference transcriptome maps for individual cell types in the retina provide unprecedented insights into the signals that define retinal cell identity and advance our understanding of the retina. This human neural retina transcriptome data can be used as a benchmark to assess the quality and maturity of pluripotent stem cell-derived retinal cells, such as retinal ganglion cells (Gill et al, 2016;Kobayashi et al, 2018;Sluch et al, 2015) and photoreceptors (Lakowski et al, 2018). We also confirmed that a relatively low level of sequencing depth (~40,232 reads per cell) is sufficient for identification and classification of major cell types in a complex tissue like retina.…”
Section: Discussionsupporting
confidence: 63%
“…For cell based therapies, it is important to generate and enrich defined populations of retinal cells of interest (e.g., photoreceptors, RPE cells) and assess their transplantation into the context of host retinal environment. Various approaches have been used to selectively enrich retinal cell types from these complex organoids including immunostaining with cell surface markers or flow activated cell sorting using reporter labeled cell lines , which harbor fluorescent markers of key photoreceptor transcription factors such as cone rod homeobox ( CRX ) or neural retina leucine zipper ( NRL ) genes. Enrichment of photoreceptors is, however, not sufficient for ensuring successful engraftment into an adult retina.…”
Section: Introductionmentioning
confidence: 99%
“…Induced pluripotent stem cell (IPSC)-derived retinal organoids have been shown to have a wide range of applications, including the study of human retinogenesis, 1-3 disease modeling, 4,5 drug discovery, 6,7 and cell therapy. [8][9][10] Numerous protocols have been developed for the generation of retinal organoids that follow basic developmental principles of forebrain development and eye formation. Despite the ability of these protocols to give rise to laminated retinal organoids, variability in the propensity of iPSCs to give rise to various retinal cell types is often reported.…”
Section: Introductionmentioning
confidence: 99%